PENERAPAN MODEL PEMBELAJARAN PROCESS ORIENTED GUIDED INQUIRY LEARNING (POGIL) TERHADAP KEMAMPUAN PEMAHAMAN KONSEP DITINJAU DARI SELF-EFFICACY SISWA KELAS VIII SMP NEGERI 2 COMAL - Puput Rakhmawati (Universitas Pekalongan, 2019)
The aims of this research are: (1) to find out whether the students’ ability to understand mathematic concept using POGIL method is better than the ability of studentswith expository learning, (2) to perceive whether the conceptual understanding of students with high self-efficacy is better than the students with medium and low self-efficacy, (3) to find out if the high self-efficacy students’ mathematic conceptual understanding ability is better by applying POGIL than expository method, if the medium self-efficacy students’ mathematic conceptual understanding ability is better by applying POGIL than expository method and if the low self-efficacy students’ mathematic conceptual understanding ability is better by applying POGIL than expository method.